Cognitive and functional connectivity alterations in Friedreich's ataxia. Issue 6 (14th April 2018) - Cocozza, Sirio; Costabile, Teresa; Tedeschi, Enrico; Abate, Filomena; Russo, Camilla; Liguori, Agnese; Del Vecchio, Walter; Paciello, Francesca; Quarantelli, Mario; Filla, Alessandro; Brunetti, Arturo; Saccà, Francesco
Abstract: Objective: The aim of this study was to perform the first resting‐state functional MRI (RS‐fMRI) analysis in Friedreich's ataxia (FRDA) patients to assess possible brain functional connectivity (FC) differences in these patients, and test their correlations with neuropsychological performances. Methods: In total, 24 FRDA patients (M/F: 15/9, mean age 31.3 ± 15.0) and 24 healthy controls (HC; M/F: 15/9, mean age 30.7 ± 15.5) were enrolled in this cross‐sectional study. All patients underwent a thorough neuropsychological battery, investigating different cognitive domains. RS‐fMRI data were analyzed using a seed‐based approach, probing the FC of cortical areas potentially referable to specific executive and cognitive functions compromised in FRDA. Results: Compared to HC, FRDA patients showed overall worse neuropsychological scores in several domains, including global cognitive assessment, spatial memory, visuoperception and visuospatial functions, and executive functions. Analysis of RS‐fMRI data showed a higher FC in FRDA patients compared to HC between paracingulate gyri and the medial frontal gryrus, between the superior frontal gyrus and bilateral angular gyri, and between the middle temporal gyrus and the cingulate gyrus, with a reduced FC between the medial frontal gryrus and the cerebellum. Interpretation: We found a reduction in FC between frontal areas and the contralateral cerebellar cortex in FRDA, in line with the known alteration in cerebello‐cortical pathway in this condition. On the other hand, a higher FC between different cortical areas was shown, possibly reflecting a compensatory phenomenon. These results, in conjunction with clinical findings, may shed new light on the pattern of supratentorial and infratentorial involvement, and on dynamics of brain plasticity in this disease.